2022
DOI: 10.3390/polym14122364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transglutaminase Pre-Crosslinking Treatment Incorporated with Glucono-δ-lactone on the Physicochemical and Digestive Properties of Tofu

Abstract: This study evaluated the effect of transglutaminase (TGase) pre-crosslinking treatment on the physicochemical and digestive characteristics of tofu coagulated by glucono-δ-lactone (GDL). Results showed that certain TGase pre-crosslinking times (0.5, 1, 2 and 3 h) could promote the colloidal stability of soymilk with increased particle average sizes and absolute values of zeta potential. Particularly, the water holding capacity and gel strength of tofu pre-crosslinked by TGase for 2 h were 6.8% and 47.7% enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…This further indicates that tofu cross‐linked by TGase and MgCl 2 is more likely to release small active peptides and is more suitable for digestion and absorption by the human body. This result is consistent with our previous study that the probability of bioactive peptide release was more remarkable in tofu prepared by first treating with TGase for 2 h, followed by the addition of glucono‐δ‐lactone, than in soymilk (Hui & Xing, 2022). Different factors can modify protein microstructures, leading to changes in their enzymatic susceptibility and influencing the release of peptides from the food matrix (Bhat et al ., 2021).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This further indicates that tofu cross‐linked by TGase and MgCl 2 is more likely to release small active peptides and is more suitable for digestion and absorption by the human body. This result is consistent with our previous study that the probability of bioactive peptide release was more remarkable in tofu prepared by first treating with TGase for 2 h, followed by the addition of glucono‐δ‐lactone, than in soymilk (Hui & Xing, 2022). Different factors can modify protein microstructures, leading to changes in their enzymatic susceptibility and influencing the release of peptides from the food matrix (Bhat et al ., 2021).…”
Section: Resultssupporting
confidence: 93%
“…The samples subjected to in vitro simulated gastrointestinal digestion were classified into four groups: (1) Soymilk (the control): soymilk without the addition of TGase and MgCl 2 ; (2) ST: soymilk with 1 h of pre‐crosslinking using TGase; (3) SM: tofu gel prepared solely by adding MgCl 2 and (4) STM: tofu gel prepared by pre‐crosslinking with TGase for 1 h followed by adding MgCl 2 . The in vitro simulated gastrointestinal digestion model established by Hui & Xing (2022) was used for the experiment, which includes the oral digestion stage (P1), gastric digestion stage (P2) and intestinal digestion stage (P3). Samples were collected at the following time points: prior to digestion (numbered P0), after oral digestion (numbered P1), after 5 and 60 min of gastric digestion (numbered P2–5 and P2–60), after 30 and 120 min of duodenal digestion (numbered P3–30 and P3–120).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro gastrointestinal simulated digestion (GIS) was carried out as the method adapted from Hui and Xing (2022) [ 39 ]. The whole in vitro GIS digestion steps are shown in Figure 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Although GdL has rarely been applied to plant-based meat, due to its positive effect on soy protein gelation, it is suggested to improve the physical properties of plant-based meat. Hui et al [ 29 ] reported transglutaminase and glucono-δ-lactone-treated tofu gel shows a slow digestion rate, and it has more chances to release bioactive peptides than soymilk.…”
Section: Introductionmentioning
confidence: 99%